Reluctant saint life of francis of assisi - Spoto, Donald (Penguin, 2002)
In Reluctant saint, Donald Spoto shows us a Saint Francis who transcends the image of Francis familiar to even the least religious among us. Spoto's unprecedented access to unexplored archives and the saint's own unpublished letters help reveal how Francis pioneered an entirely new historical movement, one that eventually slipped from his grasp. Spoto highlights Francis's position within the ecclesiastical, political, and social forces of medieval Italy in all its violence, color, and mystery. It was a time of crisis with a craving for reform and for a deeper, simpler, more personal faith--yet concern for the common good, and for the poor and sick, was virtually unknown. A key part of the revolution Francis brought about was his insistence that such concern lay at the heart of the Gospel. Reluctant saint portrays a life that has captured the hearts and minds of millions over the centuries